Measuring the Business Cycle Chronology with a Novel Business Cycle Indicator for Germany - Agnieszka Gehringer; Thomas Mayer (Journal of Business Cycle Research, 2021)
This paper introduces a Business Cycle Indicator to compile a transparent and reliable chronology of past business cycle turning points for Germany. The Indicator is derived applying the statistical method of Principal Component Analysis, based on information from 20 economic time series. In this way, the Business Cycle Indicator grasps the development of the broader economic activity and has several advantages over a business cycle assessment based on quarterly series of Gross Domestic Product.
Keywords: C14; C82; E32; E65; 330; Business cycle dating; Recession; Principal component analysis; German economy